2020
DOI: 10.1186/s12979-020-00200-1
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of T cell immunosenescence in diabetic chronic kidney disease

Abstract: Background Type 2 diabetes is an important challenge given the worldwide epidemic and is the most important cause of end-stage renal disease (ESRD) in developed countries. It is known that patients with ESRD and advanced renal failure suffer from immunosenescence and premature T cell aging, but whether such changes develop in patients with less severe chronic kidney disease (CKD) is unclear. Method 523 adult patients with type 2 diabetes were recruited for this study. Demographic data and clinical informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Various indications of immunological dysfunction, leading to infectious complications [ 33 ], including accelerated aging of the thymus and other lymphoid organs and insufficient adaptive immune response [ 34 , 35 ], characterize uremia at the systemic level. An increase in systemic proinflammatory processes is also a hallmark of this disorder, which is linked to premature body aging [ 36 ].…”
Section: General Characteristics Of the Causes And Consequences Of Esrdmentioning
confidence: 99%
“…Various indications of immunological dysfunction, leading to infectious complications [ 33 ], including accelerated aging of the thymus and other lymphoid organs and insufficient adaptive immune response [ 34 , 35 ], characterize uremia at the systemic level. An increase in systemic proinflammatory processes is also a hallmark of this disorder, which is linked to premature body aging [ 36 ].…”
Section: General Characteristics Of the Causes And Consequences Of Esrdmentioning
confidence: 99%
“…Researchers confirmed that CD153 and CD30 signaling may interact with CD153 + PD-1 + CD4 + senescence-associated T cells (SAT) and CD30 + T-bet + age-related B cells, resulting in tertiary lymphoid tissue generation in chronically inflammatory organs, thereby promoting renal inflammation and fibrosis ( 173 ). In addition to ESRD, CD8 + T cell depletion occurs as early as CKD3 in diabetes mellitus, showing the characteristics of aggravated immunosenescence ( 174 ). Moreover, the occurrence and development of kidney diseases might be associated with cardiovascular diseases.…”
Section: Immunosenescence Influences Injury and Aging Of Solid Organsmentioning
confidence: 99%
“…Overall, the activation of intracellular pathways accompanied by adipose inflammation increases the production of pro-inflammatory cytokines and promotes the infiltration of more pro-inflammatory M1 macrophages. Additionally, a hallmark in obesity and T2D are the senescent immune cells which exhibit a senescence-associated secretory phenotype (SASP) characterized by secreting a huge quantity of pro-inflammatory cytokines (IL-1β, IL-6, IL-8, IL-18, CCL-2, and TNF-α) [ 80 , 81 , 82 ]. SASP cells have enhanced mitochondrial apoptosis switching from apoptosis to pyroptosis, through a high mitogen-activated protein kinases (MAPKs) activity which drive IL-1 production (leading to auto-inflammation) and reduced IFN type 1 production, leading to a deficiency to combat viral infections [ 83 ] (see Figure 1 ).…”
Section: Immune Alterations In Obesity and T2dmentioning
confidence: 99%